Crítica de libros - Herrero de Castro, Ruben; Marquina Barrio, Antonio; Ruiz Campillo, Xira (UNISCI Discussion Papers, 2007)
Corral Salvador, Carlos (2007) : Confesiones religiosas y Estado español: Régimen Jurídico ; Mötölä, Kari (ed.) (2006) : Transatlantic Relations and Global Governance ; Merlingen, Michael y Ostrauskaitė, Rasa (2006) : European Union Peacebuilding and Policing: Governance and the European Security and Defence Policy ; Jones, Adam (2006) : Genocide: A Comprehensive Introduction